CHARACTERISATION OF FRACTURED RESERVOIRS IN THE MALAY BASIN USING SEISMIC ATTRIBUTES AND IMAGE LOGS - SHAMSUDDIN, ANNUR ASMA SAYIDAH (2019)
Finding oil in fractured basement rock in South East Asia has been a goal for several decades, but it remains a challenge for exploration and production in the Malay Basin due to its geological complexity, including rock properties and tectonics in understanding fracture characterisation.